Działalność publiczna Kurdów w Polsce na tle aktywności diaspory kurdyjskiej w Europie Zachodniej - Jomma, Fuad (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
Autorzy zadają pytania o formy i rodzaje działalności publicznej Kurdów w Polsce w ciągu ostatniego półwiecza, o wpływ transformacji ustrojowej na tą działalność, a także o różnice i podobieństwa między działalnością diaspory kurdyjskiej w Polsce i w krajach zachodnich. Posługując się analizą dokumentów i literatury naukowej oraz obserwacją działalności opisywanych przez siebie organizacji, autorzy zwracają uwagę na różnice demograficzne między diasporą polską a diasporami zachodnimi, postępujące integrowanie się działalności publicznej Kurdów w Polsce z polskim życiem publicznym oraz na problem braku umiejętności wykorzystania kapitału społecznego członków diaspory do osiągania wspólnych, długofalowych celów.

The authors raise questions about the forms and types of public activity of Kurds in Poland during the last half-century, the impact of the political transformation on this activity, and the similarities and differences between the activities of Kurdish minorities in Poland and in Western countries. On the basis of an analysis of documents and academic studies, as well as examining the organizations described, the authors point to the demographic differences between Kurdish minorities in Poland and in the West, the advancing integration of Kurdish public activity with Polish public life and, finally, the inability to use the social capital of members of this minority for achieving common, long-term goals.
Kurdish public activities in Poland compared to the activities of Kurdish minorities in Western Europe
Keywords: kultura polityczna; myśl polityczna; stosunki międzynarodowe; Europa Środkowo-Wschodnia; political culture; political thought; international relations; Central and Eastern Europe